Types of Communications Technology and Civil Conflict - Tushar Bharati; Michael Jetter; Muhammad Nauman Malik (Institute of Labor Economics (IZA), 2022)
This paper introduces a unifying theoretical framework to understand the relationship between different types of communications technology (CT) and the incidence of civil conflict. In our model, one-way CT allows the government to broadcast messages they use to (mis)inform dissidents about the size of the available rents. This decreases the dissident group's marginal returns from fighting against the government. Two-way CT facilitates dialogue among dissident group members, helping them to overcome coordination issues and improve their chances of winning a fight against the government. The model predicts one-way CT decreases and two-way CT increases conflict incidence. Empirical evidence from country-level panel databases (studying up to 189 countries) and individual-level survey responses (from up to 74 countries) is consistent with these predictions. Radio and television penetration and usage are associated with diminished levels of civil conflict and anti-government attitudes. On the contrary, cell phone and internet penetration and usage correlate with greater likelihoods of conflict and higher anti-government sentiment.
Keywords: D74; L82; O14; 330; civil conflict; communications technology; cell phones; internet; radio; television